1998
DOI: 10.1523/jneurosci.18-24-10464.1998
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Modifications in Cultured Hippocampal Neurons: Dependence on Spike Timing, Synaptic Strength, and Postsynaptic Cell Type

Abstract: In cultures of dissociated rat hippocampal neurons, persistent potentiation and depression of glutamatergic synapses were induced by correlated spiking of presynaptic and postsynaptic neurons. The relative timing between the presynaptic and postsynaptic spiking determined the direction and the extent of synaptic changes. Repetitive postsynaptic spiking within a time window of 20 msec after presynaptic activation resulted in long-term potentiation (LTP), whereas postsynaptic spiking within a window of 20 msec b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

230
3,696
10
21

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 4,052 publications
(4,065 citation statements)
references
References 67 publications
(62 reference statements)
230
3,696
10
21
Order By: Relevance
“…The parameters are c 10 = 10 5 , c 01 = 20, c 11 = 5, τ l = 25 ms, τ shift = 10 ms, τ decay = 10 5 ms, and g 0 = 0.125 nS if not stated otherwise. Because of the large value of c 01 the synaptic strength is only depressed if post-synaptic spikes are not paired with presynaptic ones, consistent with experimental observations [36,37,28,30] and biophysical models [1,52].…”
Section: Synaptic Plasticitysupporting
confidence: 80%
“…The parameters are c 10 = 10 5 , c 01 = 20, c 11 = 5, τ l = 25 ms, τ shift = 10 ms, τ decay = 10 5 ms, and g 0 = 0.125 nS if not stated otherwise. Because of the large value of c 01 the synaptic strength is only depressed if post-synaptic spikes are not paired with presynaptic ones, consistent with experimental observations [36,37,28,30] and biophysical models [1,52].…”
Section: Synaptic Plasticitysupporting
confidence: 80%
“…2). This finding is robust and has been found in neurons from the hippocampus using acute, (23) organotypic slices, (31) or dissociated cell culture, (32) and in layers V (33,34) and II/III (35) of the cerebral cortex, as well as in vivo preparations using cat (36,37) and Xenopus (38) visual systems. The temporal window permissive for LTP induction is 10-20 ms (milliseconds) whereas the window in which the presynaptic spike can follow the postsynaptic spike in order to induce LTD ranges from 20 to 100 ms in different preparations.…”
Section: Introductionsupporting
confidence: 65%
“…An influence of the temporal signal order on plasticity was proposed by Gerstner et al (1996) and experimentally confirmed by Markram et al (1997), Magee and Johnston (1997), and Bi and Poo (1998) [although Levy and Steward (1983) had already discovered this phenomenon]. These authors found that for the expression of LTP or LTD not only the activity as such matters but also the timing.…”
Section: Long-term Plasticitymentioning
confidence: 87%
“…Neural systems have several different mechanisms (Bi and Poo 1998;Turrigiano et al 1998;Royer and Paré 2003;Zhou et al 2003), which are also used in theoretical studies (Rochester et al 1956;Bienenstock et al 1982;Riedel and Schild 1992;Van Rossum et al 2000) to avoid these runaway dynamics.…”
Section: Long-term Plasticitymentioning
confidence: 99%